Postharvest methyl jasmonic acid and hot water can reduce the internal breakdown and quality loss of apricot fruit at shelf life - Ezzat, A. (International Journal of Horticultural Science, 2020)
The aim of this study was to investigate the postharvest effect of methyl jasmonic acid (MJ) and hot water on internal break-down and quality loss of apricot fruit under shelf life conditions. Cultivar Flavor cot apricot fruit were used to treat with water as control treatment, with 0.2 mmol/L MJ and with hot water 35 oC for 5 min. Fruit were stored at room temperature and were examined every 2 days for internal break-down and quality loss. Results showed that treated fruits with MJ and hot water showed the lowest weight loss and the highest firmness during all assessment times. Control fruits showed losing of customer acceptance from the day 2 of shelf life and then decreased dramatically to approximately loss all the acceptance at day 8. The SSC showed sever reduction in untreated fruit after day 6 at shelf life. Total phenol content reduced and polyphenol oxidase (PPO) increased in all assessment times for all treatments. Meanwhile MJ showed the best values for phenol content and lowest PPO activity. The results supported the idea of using some elicitors like methyl jasmonic and hot water treatments to enhance shelf life of apricot fruit.